DETERMINING STRATEGIC PRIORITIES FOR FORMING STATE POLICY TO PROVIDE FINANCIAL AND ECONOMIC SECURITY UNDER MARTIAL LAW - Svitlana Kryshtanovych; Oksana Syniuk; Sergiy Yadukha; Andrii Blyznyuk; Oksana Bashtannyk; Vitalii Ravliuk (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The introduction of martial law will significantly change the modern vision of the formation of state policy to ensure financial and economic security. Today, more than ever, intensifying ways to strengthen the financial and economic security of the state is becoming priority number one. The purpose of the article is to present a modern approach to determining strategic priorities for the formation of state policy to ensure financial and economic security in conditions of martial law, which, unlike similar ones, should be characterized by the use of modern modelling methods that form the basis for developing an effective policy under current conditions, taking into account a significant number factors and variables The object of the study is the state policy of ensuring the financial and economic security of Ukraine. The research methodology involves the use of both theoretical and mathematical methods, which made it possible to form a modern model for determining strategic priorities for building an effective state policy to ensure financial and economic security. As a result, we presented not only the most modern model thanks to effective modelling methods but also what needs to be done today, to understand what strategic decisions should be made in order to form the most effective government policy to ensure financial and economic security in war conditions. condition. The study has a limitation in the form of not taking into account all possible variables and factors influencing the formation of state policy to ensure financial and economic security. Prospects for further research are to explore ensuring the financial and economic security of the state at the tactical operational level.